(untitled) (Research, Society and Development, 2022)
Objective: To identify the ideal and/or most suitable masticatory function assessment methodology or treatment for each group of patients. Material and Methods: A survey was carried out in the MEDLINE, Science Direct, and Embase databases for articles published since 1990. The articles were initially selected by their titles and abstracts, and after application of inclusion and exclusion criteria, some were selected for full text reading. The studies were submitted to qualitative, quantitative, and bias analysis. Results: Of the 1,514 studies retrieved in the initial search, 51 were selected for complete analysis. Advantages of the test foods Optocal and Optosil included reliability and standardization capacity, while their disadvantages included high processing time and hardness. Wax was mentioned for its ease of chewing and testing speed, with the disadvantages of handling and the influence of temperature, in addition to low palatability. Chewing gum exhibited a speedy and easy way of testing, low cost, and reliability, in addition to commercial availability. Conclusion: Among the existing methodologies, those that were used in few studies or not validated require additional data, and for now, their indication is not recommended. Optocal and Optosil should be indicated for patients who do not have impaired chewing function. Chewing gum is a more suitable test food for patients with impaired chewing. Its practicality in being used in tests and evaluation of results makes it a more comprehensive indicator for different types of patients, treatments, or needs to assess masticatory function.